How effective are adaptation practices on offsetting sorghum and millet yield reductions under climate change? A Systematic Review Protocol - Akponikpè, Pierre B.I.; Allakonon, M.G.B.; Zakari, Sissou; Orou, B.Z.S.; Bosire, Caroline K. (CGIAR System Organization, 2025)
Sorghum and millet play a crucial role in ensuring food security and economic resilience in semi-arid regions. However, the growing challenges posed by climate change threaten their productivity, raising concerns about how to sustain and improve yields in both the near and distant future. To mitigate these impacts, various agronomic adaptation strategies have been introduced, including for instance conservation tillage, adjusted planting schedules, drought-tolerant crop varieties, and efficient irrigation methods. While numerous studies have demonstrated the effectiveness of these strategies in reducing climate-related yield losses in staple cereals such as maize, rice, and wheat, research on their benefits for semi-arid crops (sorghum and millet) remains scarce. This systematic review (SR) seeks to quantify and synthesise the effect of adaptation practices on sorghum and millet yields under changing climatic conditions. We aim for this synthesis to provide insights into the most suitable practices for different regions and crop types, supporting sustainable agricultural management, future food security, and economic development.